2014
DOI: 10.1080/08985626.2014.985740
|View full text |Cite
|
Sign up to set email alerts
|

Culture, entrepreneurship and uneven development: a spatial analysis

Abstract: Interest in the proposed connection between culture and entrepreneurship has grown significantly in recent years. However, less attention has been given to the nature of the overall impact of this proposed association on development outcomes, particularly at a local level. In response, this paper analyses the relationship between the nature of the culture, entrepreneurship and development experienced across localities, proposing that the link between culture and development is mediated by entrepreneurship. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 155 publications
0
48
0
5
Order By: Relevance
“…A significant body of research on immigrant entrepreneurs has identified culture as one of the main forms of capital for entrepreneurs (Watts et al 2007;Sabah, Carsrud, and Kocak 2014). the cultural resources have been identified by past research as both enablers and obstacles for MWEs (Dhaliwal and Kangis 2006;pécoud 2010;Azmat 2013;Huggins and thompson 2014). For example, some authors have indicated that ethnic minority businesses capitalize on cultural characteristics such as their social capital, linguistic skills, cultural knowledge and ethnic contacts to gain a competitive advantage (Kupferberg 2003;Dhaliwal and Kangis 2006;verduijn and Essers 2013).…”
Section: Mixed Embeddedness Theory Explaining the Entrepreneurship Ofmentioning
confidence: 99%
“…A significant body of research on immigrant entrepreneurs has identified culture as one of the main forms of capital for entrepreneurs (Watts et al 2007;Sabah, Carsrud, and Kocak 2014). the cultural resources have been identified by past research as both enablers and obstacles for MWEs (Dhaliwal and Kangis 2006;pécoud 2010;Azmat 2013;Huggins and thompson 2014). For example, some authors have indicated that ethnic minority businesses capitalize on cultural characteristics such as their social capital, linguistic skills, cultural knowledge and ethnic contacts to gain a competitive advantage (Kupferberg 2003;Dhaliwal and Kangis 2006;verduijn and Essers 2013).…”
Section: Mixed Embeddedness Theory Explaining the Entrepreneurship Ofmentioning
confidence: 99%
“…But entrepreneurship carries the power to change things. Higgins and Thompson (2014) show how entrepreneurship mediates the relationship between what they term community culture and local, social and economic development. Vestrum's (2014) work on community entrepreneurship shows how a community entrepreneur brought fresh ideas and energy to the local community and stimulated social change.…”
Section: Place As Context For Meanings and Entrepreneurial Practicesmentioning
confidence: 99%
“…Amin & Thrift, 1995;Kemeny, 2012;Huggins & Thompson, 2014a;2014b;. Theory in this area has considered many potential topics, but amongst the most important has been social capital.…”
Section: Intangibles Institutions and Innovationmentioning
confidence: 99%
“…Firm level studies have begun to investigate the relationship between personality and innovation (Fitjar & Rodríguez-Pose 2011), the related field of culture is an important area of research (Huggins & Thompson, 2014a;2014b;, and psychologists have considered how the geographical distribution of entrepreneurial personalities influences entrepreneurship (Obschonka et al, 2015). But the key question -how the geography of personality influences the geography of innovationhas gone unanswered.…”
Section: Introductionmentioning
confidence: 99%